Genetic diversity in Asblack sheep (Ovis aries) of Lima, Peru by microsatellite markers - Morón Barraza, Jonathan Alejandro (2020)
The Asblack sheep is the cross of Assaf and Blackbelly to obtain a composite breed. The aim of this study was to determine the genetic diversity of the Asblack and its relationship with the parental breeds. Blood samples were taken from 103 unrelated sheep from the Lima, Peru region. Sheep samples were genotyped for 17 microsatellite markers. High diversity was found in the populations and a total of 146 alleles were detected. Asblack had the highest number of alleles. The expected heterozygosity was greater than the observed in Asblack sheep with regards to Assaf and Blackbelly which indicates a trend for a deficit of heterozygotes in the cross. In addition, nine loci were not in Hardy-Weinberg equilibrium, under the null hypothesis of random union of gametes in the cross. The molecular variation among the populations was 11.4% and the variation among individuals within the populations was 6.81% of the total; however, when analyzing the population structure, the genetic flow was 0.03, which indicates a lower genetic differentiation. The values ​​of FIS (0.077) reflected low levels of inbreeding, and FST (0.115) indicates a moderate genetic differentiation. On the other hand, the populations were separated in the three clusters (K​=3), a result supported by the factorial correspondence analysis. In conclusion, a high genetic diversity was found in the populations studied by breed and individuals, with a moderate differentiation of Asblack sheep with its parental breeds.